Real world study of the continuation of bevacizumab beyond disease progression after first‐line treatment containing bevacizumab in Chinese patients with advanced non‐small cell lung cancer. Issue 12 (16th October 2018) - Xing, Puyuan; Mu, Yuxin; Wang, Yan; Hao, Xuezhi; Zhu, Yixiang; Hu, Xingsheng; Wang, Hongyu; Liu, Peng; Lin, Lin; Wang, Zhijie; Li, Junling
Abstract : Background: Bevacizumab (Bev) plus platinum‐based chemotherapy is a standard first‐line treatment option for advanced non‐squamous non‐small cell lung cancer (NS‐NSCLC). We evaluated the efficacy and safety of continuing Bev in Chinese patients with advanced NS‐NSCLC progression after first‐line treatment containing Bev in a real‐world setting. Methods: The data of 118 patients with advanced NS‐NSCLC who received Bev between July 2009 and July 2017 were retrospectively collected. The patients were divided into groups: 15 in Bev first‐line, 82 in Bev ≥ second‐line, and 21 in Bev cross‐lines. The primary endpoint was overall survival; secondary objectives were progression‐free survival, objective response rate, disease control rate, and safety. Results: The overall survival was 21.8, 32.5, and 18.9 months ( P = 0.092) in the overall population and 39.3, 25.8, and 15.0 months ( P = 0.347) in the wild‐type population in the Bev first‐line, Bev ≥ second‐line, and Bev cross‐lines groups, respectively. There were no significant differences in progression‐free survival of second‐line treatment between the groups in the overall population: 2.6, 3.7, and 3.2 months in the Bev first‐line, Bev ≥ second‐line, and Bev cross‐lines groups, respectively ( P = 0.796). No statistically significant improvement in objective response or disease control rates in the Bev cross‐lines group was observed. No unexpected or severe adverse events were recorded. Conclusion: We found no benefit in continuing Bev treatment beyond progression after first‐line treatment containing Bev for patients with advanced NS‐NSCLC. Further research of validated predictive biomarkers of response to treatment after long‐term antiangiogenic therapy is required.